2024
DOI: 10.1039/d3nj05740b
|View full text |Cite
|
Sign up to set email alerts
|

Tailored design, synthesis, and catalytic aspects of mononuclear cis-dichloro copper(ii) complexes with simple DPA-derived tridentate ligands and their biomimicking activities

Arabinda Muley,
Kalai Selvan Karumban,
Sadananda Kumbhakar
et al.

Abstract: Activation of molecular oxygen remains a pertinent challenge to the scientific community due to their poor selectivity especially towards organic substrates. In biological systems, phenoxazinone synthase and catechol oxidase are...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 77 publications
0
3
0
Order By: Relevance
“…60 The distance between the copper and nitrogen centers are ∼1.9–2.1 Å. Pentacoordinated copper complexes have shown similar bond lengths to the metal center with the Cu–N bonds varying within 1.96 Å to 2.37 Å. 34,48,61–63 Polyhedral views and the packing along the b -axis are given in Fig. S11–S13 †…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…60 The distance between the copper and nitrogen centers are ∼1.9–2.1 Å. Pentacoordinated copper complexes have shown similar bond lengths to the metal center with the Cu–N bonds varying within 1.96 Å to 2.37 Å. 34,48,61–63 Polyhedral views and the packing along the b -axis are given in Fig. S11–S13 †…”
Section: Resultsmentioning
confidence: 99%
“…40–42 Despite few reports, the complexes derived from DPA-based ligands have an immense scope for numerous applications. 43–48…”
Section: Introductionmentioning
confidence: 99%
“…21,32–35 However, reports on mononuclear Cu( ii ) complexes are comparatively less. 36–39 Various bioinspired PHS model systems targeting the structural and operational aspects of PHS have been developed in recent years. A tetranuclear model complex (first report in this regard) containing a cubane-like Cu( ii ) core in coordination with a redox-active ligand core that can catalyse the oxidation reaction of OAPH to APX was documented by Chaudhuri et al 40 Furthermore, similar tetranuclear complexes were reported by several research groups as suitable PHS mimicking catalysts.…”
Section: Introductionmentioning
confidence: 99%